Ectopic Hepatocellular Carcinoma Arising from the Peritoneum in a Patient with a History of Oropharyngeal Cancer: A Case Report - Lee, Ji Young (Case Rep Oncol, 2015)
A subphrenic mass was noted on a surveillance computed tomography (CT) scan of a 65-year-old man who had achieved complete remission of oropharyngeal cancer after concurrent chemoradiotherapy. The mass was 3.2 cm in size and showed a multilobular enhancing pattern along the peritoneal lining. The patient was negative for hepatitis B surface antigen and anti-hepatitis C virus antibody. His carcinoembryonic antigen level was within the normal range. Contrast-enhanced CT revealed no mass in the liver. He underwent surgery, and a pale yellowish soft tumor measuring 3.8 × 3.2 × 1.2 cm was resected. Histologically, the tumor was confirmed to be a hepatocellular carcinoma. Currently, he is doing well, and has been followed up without any signs of recurrence.